Increased radiation-associated T-cell infiltration in recurrent IDH-mutant glioma - Makarevic, Anastasia; Rapp, Carmen; Dettling, Steffen; Reuss, David; Jungk, Christine; Abdollahi, Amir; Deimling, Andreas von; Unterberg, Andreas; Herold-Mende, Christel; Warta, Rolf (International journal of molecular sciences, 2020)
Most gliomas are associated with a fatal prognosis and remain incurable because of their infiltrative growth. Consequently, the addition of immunotherapy to conventional therapy may improve patient outcomes. Here, we analyzed T-cell infiltration and, therefore, a major prerequisite for successful immunotherapy in a series of primary (n = 78) and recurrent (n = 66) isocitrate dehydrogenase (IDH)-mutant glioma and their changes following treatment with radio- and/or chemotherapy. After multicolor immunofluorescence staining, T cells were counted in entire tumor sections using a software-based setup. Newly diagnosed diffuse IDH-mutant gliomas displayed a median T-cell infiltration of 0.99 T cells/mm2 (range: 0–48.97 CD3+ T cells/mm2), which was about two-fold increased for CD3+, helper, and cytotoxic T cells in recurrent glioma. Furthermore, T-cell infiltration of recurrent tumors was associated with the type of adjuvant treatment of the primary tumor. Interestingly, only glioma patients solely receiving radiotherapy presented consistently with increased T-cell infiltration in their recurrent tumors. This was confirmed in a subset of 27 matched pairs. In conclusion, differences in the T-cell infiltration of primary and recurrent gliomas were demonstrated, and evidence was provided for a beneficial long-term effect on T-cell infiltration upon treatment with radiotherapy.